2017
DOI: 10.5114/hpr.2017.68235
|View full text |Cite
|
Sign up to set email alerts
|

Partner support as a mediator of the relationship between prenatal concerns and psychological well-being in pregnant women

Abstract: health psychology report • volume 5(4), 7 original article background Pregnant women's psychological well-being affects their emotional state, which in turn has a significant impact on fetal development, the course of labor, and the mother's adaptation in the postpartum period. Social support, especially partner support, is proven to have a protective effect against stress, worries, and concerns that occur in pregnancy. The main objective of this study was to investigate whether support received from the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Many studies have shown that during pregnancy women's mental health is associated with social support [8][9][10], marital relationships [11], as well as socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that during pregnancy women's mental health is associated with social support [8][9][10], marital relationships [11], as well as socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review marital relationships and social support were reported to be important determinants for maternal mental health during pregnancy [1]. Other studies have also shown that social support, especially the partner's, is of great importance in maintaining the mental health of pregnant women [8,17,18]. Further, affecting the marital relations, the partner's emotional support has important effects on the mental health of women during pregnancy [9,10] in such a way that some studies have reported that the partner's emotional support has a positive relation to increased marital satisfaction in women [19].…”
Section: Introductionmentioning
confidence: 99%
“…Having close, supportive ties with others can have a significant positive effect on health, physiological response to psychological stressors (including better functioning of the immune system and reduced cardiovascular reactivity), coping with illness and stress, and promoting longevity (for reviews, see Dickerson & Zoccola, 2011;Uchino, 2006). Researchers have focused on the importance of social support for the functioning of individuals in many contexts of family life associated with stress, such as coping with serious illness and recovering (Luszczynska, Boehmer, Knoll, Schulz, & Schwarzer, 2007;Ogińska-Bulik, 2013;, coping with aging (Acitelli & Antonucci, 1994;Cutrona, Russell, & Rose, 1986), dealing with the consequences of divorce and successfully adjusting to post-divorce life (Amato, 2000;Kołodziej-Zaleska & Przybyła-Basista, 2016), bringing up children with special needs or disabilities (Barnett, Clements, Kaplan-Estrin, & Fialka, 2003;Findler, Jacoby, & Gabis, 2016;Kózka & Przybyła-Basista, 2018), and functioning of women during pregnancy and the postpartum period (Dunkel-Schetter, Sagrestano, Feldman, & Killingsworth, 1996;Ilska & Przybyła-Basista, 2017;Maliszewska, Bidzan, Świątkowska, & Preis, 2016;Rini, Dunkel-Schetter, Hobel, Glynn, & Sandman, 2006;Negron, Martin, Almog, Balbierz, & Howell, 2013). In all these contexts of overcoming life's hardships, social support can prove crucial for ensuring health and well-being, as well as finding effective ways of coping with stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies aimed to determine factors which affect the mental health of pregnant women. Many studies have shown that during pregnancy women's mental health is associated with social support [7][8][9], marital relationships [10], as well as socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review marital relationships and social support were reported to be important determinants for maternal mental health during pregnancy [1]. Other studies have also shown that social support, especially the partner's, is of great importance in maintaining the mental health of pregnant women [7,16,17]. Further, affecting the marital relations, the partner's emotional support has important effects on the mental health of women during pregnancy [8,9] in such a way that some studies have reported that the partner's emotional support has a positive relation to increased marital satisfaction in women [18].…”
Section: Introductionmentioning
confidence: 99%